1986
DOI: 10.1038/320065a0
|View full text |Cite
|
Sign up to set email alerts
|

Structural alteration of hair cells in the contralateral ear resulting from extracochlear electrical stimulation

Abstract: Chronic electrical stimulation of the auditory nerve in patients with profound sensori-neural deafness is becoming increasingly routine. Therefore, it is important to understand more about the long-term consequences of this procedure. Hitherto, structural studies in animals after electrocochlear stimulation have concentrated on the stimulated cochlea. Here we have examined the effects of unilateral extracochlear electrical stimulation on the spiral organ of both the ipsilateral and contralateral ears of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This relation was stronger in subjects that received the individualized masking map due to significant electric masking. This effect might result in better overall performance after longer adjusting times and could help to preserve residual hearing by better training effects and less possible adverse electric stimulation ( Dodson et al 1986 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This relation was stronger in subjects that received the individualized masking map due to significant electric masking. This effect might result in better overall performance after longer adjusting times and could help to preserve residual hearing by better training effects and less possible adverse electric stimulation ( Dodson et al 1986 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results might indicate that a fitting strategy with less electric stimulation in the apical region is feasible for the clinical practice, as it reduces the amount of electric current the surviving hair cells are exposed to. As Dodson et al (1986) showed damage to the outer hair cells and the efferent functionality of the cochlear nerve due to loud electric stimulation, implementing a reduction of stimulation of apical electrodes in a standard fitting practice could help to protect outer hair cells in the long-term. Coco et al (2007) did not find an effect of chronic suprathreshold electric stimulation on the survival of inner and outer hair cells, however, they did not address the status of the hair cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At higher levels of ACh (100 μM), slow changes in the potassium currents and in the outer hair cell motility suggest that calcium release and activation of an enzyme cascade may occur (Dallos et al 1997). Evidence from whole‐animal experiments further suggests that an abnormal patterning of efferent stimulation may lead to degenerative changes in outer hair cells (Dodson et al 1986). In such experiments where the auditory system is stimulated by an indwelling unilateral electrode, alterations of the outer hair cells on the contralateral side are observed.…”
Section: Discussionmentioning
confidence: 99%
“…The different effects of long-term electric and acoustic stimulation on peripheral and central auditory processing are also an important factor for influencing the ability to integrate auditory information (Gstoettner et al, 2006 ; Kronenberger et al, 2014 ; Skarzynski, 2014 ). Intense, long-term electric stimulation could cause damage in the outer hair cells and the efferent functionality of the cochlear nerve, particularly the apical regions, which results in negative neural processing in the higher auditory system (Dodson et al, 1986 ). One specific factor that affects integration for BCI users is binaural spectral mismatch, which can be evoked by various insertion depths of the electrode array into the cochlea of each ear (Yoon et al, 2011 ; Mukherjee et al, 2012 ; Mertens et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%